The Corelation Between Vulva Hygiene Knowledge and Hormonal Contraception Use with Vaginal Discharge in Women of Reproductive Age in The Work Area of Rowosari Health Center Semarang City - Anggraini, Novita Nining; Mardiyah, Dhia (Indonesian Journal of Social Science Research, 2025)
Vaginal discharge is a common reproductive health issue experienced by women of reproductive age (WRA) and can be influenced by various factors, including knowledge of vulva hygiene and the use of hormonal contraception. This study aimed to analyze the relationship between vulva hygiene knowledge and hormonal contraception use with the occurrence of vaginal discharge in WRA within the Rowosari Health Center work area, Semarang City. Methods: This research utilized an analytical design with a cross-sectional approach and involved 50 respondents selected through purposive sampling. Results: Most respondents had good knowledge of vulva hygiene (80%), although only 54% understood the importance of not excessively using antiseptic soap. Additionally, 60% of respondents experienced vaginal discharge, with the highest prevalence among users of contraceptive pills (100%) and implants (75%). Bivariate analysis revealed significant relationships between vulva hygiene knowledge (p=0.029) and hormonal contraception use (p=0.039) with vaginal discharge. Conclusion: The level of vulva hygiene knowledge and the type of hormonal contraception used significantly influence the occurrence of vaginal discharge in WRA. Enhanced education about proper vulva hygiene practices and the impact of hormonal contraception is needed to reduce the risk of vaginal discharge. This research is expected to serve as a reference for developing reproductive health programs in healthcare facilities.